European public procurement directives and their implementation in Slovenia - Stanka Setnikar Cankar; Veronika Petkovšek (Central European Public Administration Review)
This article presents the results of the research work “Awarding work to external contractors,” carried out with a questionnaire in 2009 and 2010. The research examined the method and scope of public procurement in Slovenian municipalities with more than 8000 inhabitants. The objectives of the research work were: a comparison of public procurement legislation in selected EU countries; determination of the current situation in the field of public procurement in local government in years 2008 and 2009; determination of similarities and differences in the implementation of contracts; determination of the most common open questions in the implementation of contracts; determination of good practices in public procurement and making the recommendations for changes. Public procurement represents a significant proportion of national budget spending. Municipalities allocate around 20% of all expenditures to public procurement. The scope and methods of public procurement vary between municipalities. Small-value public procurement is determined by the municipalities in their internal acts, while large-value public procurement has legally prescribed procedures. New legislation on public procurement has brought innovations in the field of public tender and contract award procedures for procurement, which enables greater flexibility in the implementation and realisation of public procurement. This article presents also the European directives on public procurement and an international comparison of public procurement in selected EU and EEA states.